THE DETERMINANTS INFLUENCING FINANCIAL PERFORMANCE OF COMMERCIAL BANKS LISTED IN NAIROBI SECURITIES EXCHANGE - ROTICH , YATICH JAMES (IJRDO - Journal of Business Management, 2019)
The intermediation role of commercial banks is bound by the extent to which its key business performance drivers are manipulated to improve on financial performance and thus the study examined the determinants influencing financial performance of commercial banks listed in NSE. The study was supported by the following specific objectives: to establish the influence of volume of deposits on financial performance of commercial banks listed in Nairobi securities exchange, to determine the influence of capital adequacy on financial performance of commercial banks listed in NSE, to examine the influence of levels of liquidity of on financial performance of commercial banks listed in NSE and to investigate the effect of the volume of loans of on financial performance of commercial banks listed in NSE. The target population for the study was all the eleven commercial banks listed in NSE covering a period of twelve years from 2005 to 2017 and thus a survey design of the eleven commercial banks listed NSE was undertaken. Secondary data obtained from published financial statements from commercial banks and annual banking supervision reports from CBK was used in the study. The study used descriptive research design to investigate the relationships between variables by use of mean, standard deviation, maximum and minimum values. Also the study used correlation analysis to evaluate the association between the independent variables and the dependent variables. Furthermore, the study used multiple regression model to examine the strength of the relationship between the dependent and the independent variables. The finding of the study illustrated that the relationship between Deposits and ROA was positive and significant. Also the relationship between deposits and ROE was established to be positive and significant. The study found out that the relationship between capital adequacy and both ROA and ROE was insignificant. Also, the study findings revealed that the relationship between liquidity and both ROA and ROE was statistically insignificant. The findings of the study indicated that, the relationship between loans and ROA was positive and significant at 0.01 levels while the relationship between loans and ROE was also found to be positive and significant at 0.05 levels. The study concluded that management of commercial banks should institute sound policies aimed at attracting and retaining deposits besides growing of quality loan book so as to improve on financial performance. Furthermore the study concluded that commercial banks should strive to attain minimum statutory capital adequacy and liquidity requirements.